PENAFSIRAN HUKUM TERHADAP ITIKAD TIDAK BAIK PADA PASAL 21 UNDANG UNDANG NOMOR 20 TAHUN 2016 DALAM PENGAJUAN MEREK GEPREK BENSU - Hawila Winona Lakusa (2022)
Trademark owners must register their trademarks with the Directorate General of Intellectual Property (DJKI) to obtain legal power and certainty because Indonesia adheres to a first to file system. Therefore, regulations are made to reject applications for trademarks that have the same elements in principle or in their entirety as previously registered trademarks and reject applications from applicants who have bad faith. This paper wants to interpret what good faith is contained in Article 21 Paragraph 3 of Law Number 20 of 2016 concerning Marks and Geographical Indications (hereinafter referred to as the Trademark Law) and to find out the indicators of bad faith assessment according to the DJKI and to know the extent of Article 21 Paragraph 3 of the Law. This brand has been effectively implemented. The methodology used is the methodology of legal interpretation (Legal Interpretations). The element of bad faith has been explained in Article 21 Paragraph 3 of the Trademark Law and can be interpreted through several methods. However, in its system, the DJKI cannot immediately reject the application, even though the application has elements of similarity in principal and in its entirety, the DJKI must wait for a report stating its objections before it can follow up on the objection. As well as the absence of a review team authorized to review data from applicants who registered their trademarks, Article 21 of the Trademark Law has not been effectively implemented.